THE INFLUENCE OF BPI PROGRAM ACTIVITY AND DISCIPLINE WORSHIP STUDENT ACHIEVEMENT AT RIAU JUNIOR HIGH SCHOOL - Irma Suryani; Risnawati Risnawati; Nasir Za’ba (UIR PRESS, 2024)
The purpose of this study is to find the influence of BPI activeness and worship discipline on learning achievement in Islamic Religious Education lessons. The survey method was used in this study. The number of samples studied was 30 students of the Integrated Islamic Junior High School in Kampar. The results of the research obtained are as follows: BPI activeness and worship discipline have a significant influence on PAI learning achievement. The test results obtained that the value of F = 6.821 and Sig. 0.004 < 0.05. There is no significant effect of BPI activeness on PAI Learning Achievement. The results showed that tilapia t = 0.615 and Sig. = 0.544 > 0.05. There is a significant influence of Worship Discipline on PAI Learning Achievement. The test results obtained the results that the value of t = 2.596 and Sig. 0.015 < 0.05.